Strategi ekspansi usaha dan pengelolaan kas berbasis teknologi informasi pada era new normal - Fidiana, Fidiana; Ariestianti, Widhi; Retnani, Endang Dwi; Widyawati, Dini (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Handicraft SMEs are one of the sectors affected by the Covid-19 pandemic. The implementation of this community service activity aims to offer the right expansion strategy for MSMEs affected by the Covid-19 pandemic. The scope of community service activities is limited to the Sukolilo Surabaya Handicraft SMEs. Some MSMEs have managed to survive and some have been less fortunate. The method of activity is to provide recommendations through virtual assistance activities through zoom and WhatsApp social media related to strategies to increase business and manage finances during the new normal era. The results of this community service activity include several MSMEs responding by diversifying their products and businesses. Second, partners with marketing problems have created accounts through the Instagram and Facebook applications and have participated in the exhibition agenda. Third, partners with financial problems have carried out simple financial management manually and using the SME Accounting application.